PENERAPAN MACHINE LEARNING DALAM PENGELOMPOKKAN WILAYAH RAWAN TINDAK KEJAHATAN DI KOTA BATAM MENGGUNAKAN ALGORITMA K-MEANS - Aritonang, Mega Christy; Alfannisa Annurrullah Fajrin (LPPM Universitas Putera Batam, 2024)
Issues of public security are becoming more complex in this day and age of rapid technical advancement due to the rise of societal problems including deviant behavior and social behavior as well as the collapse in moral nationalism. This has contributed to a troubling rise in crime in a number of places, including Batam City. Although Batam City is growing quickly, crime is also rising, particularly in areas that are seen to be vulnerable. Crimes including motor vehicle theft, violent theft, and aggravated theft are on the rise, according to police data. Purpose of this research is to help law enforcement Batam City take proactive measures to lower crime rates by applying machine learning techniques utilizing the k-means algorithm.